PROTECTIVE EFFECT OF IONIDIUM SUFFRUTICOSUM ON SPERMATOTOXICITY INDUCED BY ETHANOL IN EXPERIMENTAL RATS - M.SHANMUGASUNDARAM; CHRISTILDA FELICIA JABAKANI; S.SUNDARAPANDIAN; D. BALAKRISHNAN (International Journal of Pharma and Bio Sciences, 2015)
Chronic ethanol consumption associated with infertility in Wistar rats. To evaluate the protective effect of Ionidium Suffruticosum (I.S) on Sperm parameters in ethanol intoxicated experimental models. A total of 24 rats were equally divided into four groups. Group I control, Group II received ethanol in drinking water for 16 weeks. Group III received ethanol and simultaneous administration of Ionidium Suffruticosum extract (100 mg/kg body weight) for 16 weeks. Group IV received ethanol simultaneous administration of Ionidium Suffruticosum extract (300 mg/kg body weight) for 16 weeks. group II treated with ethanol shown significantly (p<0.001) reduced sperm count, motility, viability and increased abnormal morphology when compared to control. Treatment groups III & IV significantly increased (p<0.05) the sperm count, motility, viability, and retrieved the morphological abnormalities. Ionidium Suffruticosum plays major role in the reversal of the spermatogenesis in the ethanol intoxicated experimental model.